Glucosamine protects against radiation‐induced lung injury via inhibition of epithelial‐mesenchymal transition. Issue 18 (22nd July 2020) - Lei, Xiao; Ma, Na; Liang, Yanjie; Liu, Junyan; Zhang, Pei; Han, Yanan; Chen, Wei; Du, Lehui; Qu, Baolin
Abstract: Radiotherapy is one of the most important treatments for chest tumours. Although there are plenty of strategies to prevent damage to normal lung tissues, it cannot be avoided with the emergence of radiation‐induced lung injury. The purpose of this study was to investigate the potential radioprotective effects of glucosamine, which exerted anti‐inflammatory activity in joint inflammation. In this study, we found glucosamine relieved inflammatory response and structural damages in lung tissues after radiation via HE staining. Then, we detected the level of epithelial‐mesenchymal transition marker in vitro and in vivo, which we could clearly observe that glucosamine treatment inhibited epithelial‐mesenchymal transition. Besides, we found glucosamine could inhibit apoptosis and promote proliferation of normal lung epithelial cells in vitro caused by radiation. In conclusion, our data showed that glucosamine alleviated radiation‐induced lung injury via inhibiting epithelial‐mesenchymal transition, which indicated glucosamine could be a novel potential radioprotector for radiation‐induced lung injury.